Food and feeding behaviour of Mozambique tilapia (Oreochromis mossambicus Peters) from Borna Reservoir of Maharashtra, India - Sakhare, Vishwas Balasaheb; Jetithor, Shivaji Gyanba (Journal of Fisheries, 2016)
The food analysis of 80 specimens of Oreochromis mossambicus collected from Borna Reservoir of Maharashtra, India revealed that the food of juveniles mainly consisted of rotifers (35%), followed by copepods (30%), Chlorophyceae (20%), Bacillariophyceae (10%) and aquatic insects (5%). While the food items recorded in the gut of adults were Chlorophyceae (40%), followed by Bacillariophyceae (30%), rotifers (15%), copepods (10%) and aquatic insects (5%). During present study it was found that the juveniles of O. mossamobicus mainly feed on zooplankton, and adults on phytoplankton. Intense feeding was noticed during summer season and juveniles were the active feeders.